(untitled) (Ciudades, 2017)
Proximity to retail is a key factor for population, including multiple dimensions for cities, public space vitality and social equity. This study analyses how accessibility measures can be the base to support retail within the current legal context. First, it is argued how the notion of accessibility connects to the “overriding reasons relating to the public interest” that the European Directive 2006/123 “Bolkestein” allows to invoke. Proposals of indicators for retail –including diverse targets and approaches– are evaluated according to their utility and appropriateness, as well as potentiality to be included into both retail and urban planning regulations.